Answer :
Answer:
x=3
Step-by-step explanation:
We want to solve the equation:
[tex]5 + 20 \times {2}^{2 - 3x} = 10 \times {2}^{ - 2x} + 5[/tex]
We subtract 5 from both sides to get:
[tex]20 \times {2}^{2 - 3x} = 10 \times {2}^{ - 2x} [/tex]
We divide both sides by 10 to get:
[tex]2 \times {2}^{2 - 3x} = {2}^{ - 2x} [/tex]
[tex] {2}^{1} \times {2}^{2 - 3x} = {2}^{ - 2x} [/tex]
We now simplify LHS using the product rule:
[tex] {2}^{1 + 2 - 3x} = {2}^{ - 2x} [/tex]
Since the base is the same on both sides, we equate the exponents to get:
[tex]1 + 2 - 3x = - 2x[/tex]
[tex]1 + 2 = - 2x + 3x[/tex]
[tex]x = 3[/tex]
Answer:
the answer is 3
Step-by-step explanation:
hope this is helpful :)))))))))))))